The pathological psychological dependence as an interdisciplinary problem - I. L. Andreev (Ассоциация независимых экспертов «Центр изучения кризисного общества» (in English: Association for independent experts “Center for Crisis Society Studies”), 2015)
The interdisciplinary nature of the problem of pathological mental dependency is shown in the context of the proliferation of compulsive gambling and nomophobia. The causes and consequences of behavioral dependencies are considered in the context of global changes in individual and interpersonal human consciousness of the consumer and information society. The article considers the ways and possibilities of the system solution of the problem.